The Sovereign Ascendant: Financial Collapse, Status Anxiety, and the Rebirth of the Sovereign Citizen Movement - Hodge, Edwin (Frontiers in Sociology, 2019)
As many scholars have noted, periods of economic or social unrest often bring about the growth or resurgence of extremist social movements on both the political left and the right. The 1990s saw the rise of the American militia movement, largely in response to the emergence of international organizations such as the North American Free Trade Agreement, the General Agreement on Tariffs and Trade, and an increasingly internationalist American administration. Earlier still, during the agricultural depression of the 1920s, the chaotic social, political and economic order proved to be fertile ground for the resurgent Ku Klux Klan. In the years immediately following the global financial collapse of 2008, the United States – and to a lesser extent Canada – saw the resurgence of the Sovereign Citizen movement, a puzzling, conspiratorial social and political philosophy that sought to emancipate its adherents from the tyranny of an oppressive, dictatorial, and increasingly unstable system of corrupt and illegitimate states. This paper examines the origins of the Sovereign Citizen movement and illustrates the ways in which the movement’s members deploy a radical concept of citizenship, rooted in conspiratorial thinking and often in direct conflict with the state to help manage status anxiety and uncertainty.